The effects of visual training on vision functions and shooting performance level among young handball players - Alfailakawi, A. (Science, Movement & Health, 2016)
Aim: Vision is the most dominant sense, with 70% of all sensory receptors in the eye. Vision, with components such as visual skills, contributes up to 80% of information obtained. The purpose of this study was to assess the impacts of the visual training program on vision functions and shooting skill among young basketball players. Methods: The sample consisted of 20 young handball players under 16 age (15.89 ± 1.36 years old; 175.16 ± 6.06 cm height; and 71.47 ± 5.51 kg weight), Training experience of all the participants ranged from 4 to 5 years. Subjects and coaches were required to read and complete a health questionnaire and informed consent document; there was no history of injuries, diabetes or recent surgery. All statistical analyses were calculated by the SPSS statistical package. The results are reported as means and standard deviations (SD). Differences between two groups were reported as mean difference ±95% confidence intervals (meandiff ±95% CI).Student`s t-test for independent samples was used to determine the differences in vision parameters between the two groups. The p<0.05 was considered as statistically significant. Results: - There are significant differences at 0.05 between pre and post -tests of the experimental group in all visual functions variables, and shooting skillfor the post -tests.- There are significant differences at 0.05 between pre and post -tests of the control group in the eye and hand coordination, the eye and foot coordination and visual acuity, and no significant differences in the other visual functions and shooting skill. - There are significant differences at 0.05 when the post -tests of control and experimental groups in all visual functions variables, and shooting skill for the post tests except the eye and foot coordination, visual acuity and visual depth perception from a distance of 10 cm. Conclusions: Visual training program proved an effectiveness in improving the visual functions and shooting skill among young handball players.